1999
DOI: 10.1007/s004670050574
|View full text |Cite
|
Sign up to set email alerts
|

Pulse cyclophosphamide for steroid-resistant focal segmental glomerulosclerosis

Abstract: We report the response of ten patients (6 male, 4 female) with steroid-resistant focal segmental glomerulosclerosis (FSGS) to treatment with intravenous pulse cyclophosphamide (IVCP) together with oral prednisone. All patients had been treated with 60 mg/m2 oral prednisone daily for 2 months upon initial presentation. IVCP was given monthly at a dose of 500 mg/m2 over 6 months. Oral prednisone was given concurrently at 60 mg/m2 daily for 2 months and then on alternate days for 4 months, followed by 30 mg/m2 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 22 publications
2
23
2
1
Order By: Relevance
“…Furthermore, the proportion of patients whose condition was initially steroid resistant was 36.7% in the study reported here compared with 75% in the previous report [11]. Since patients with an initially steroid-resistant condition are considered less likely to respond to treatment [7,8,11,17], the inclusion of more subjects with late resistance in our study here might have influenced the results.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Furthermore, the proportion of patients whose condition was initially steroid resistant was 36.7% in the study reported here compared with 75% in the previous report [11]. Since patients with an initially steroid-resistant condition are considered less likely to respond to treatment [7,8,11,17], the inclusion of more subjects with late resistance in our study here might have influenced the results.…”
Section: Discussioncontrasting
confidence: 71%
“…While patients with MCD and late resistance are believed to respond satisfactorily to immunosuppressive therapy [7,22], we could not show a differential response based on histology or pattern of resistance, perhaps due to the small number of subjects. While there was a trend towards an earlier age of onset in patients showing complete or partial remission than in those with no response, differences between the groups were not significant.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Although its natural course has been well described, its treatment is still a matter of debate (4)(5)(6)(7)(8)(9)(10)(11)(12). Prednisone is the initial treatment and its therapeutic response seems to be the best predictor of outcome.…”
Section: Introductionmentioning
confidence: 99%